2022
DOI: 10.6007/ijarbss/v12-i9/14859
|View full text |Cite
|
Sign up to set email alerts
|

Discovering The Relationship between Communication Strategies and Fear of Oral Presentation among University Students

Abstract: Effective public speaking is a necessary and desired ability that university graduates need to possess. This is to build into them a sense of confidence and success in communicating in today's challenging, evolving and borderless working world. However, fear or anxiety among university students still prevails and affects the way they communicate, and thus they utilise communication strategies (CS) to help them communicate orally effectively. There are multiple triggers of learners' fear of public speaking whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, L4 could see some changes in certain groups of learners and she also shared how other learners did not improve their presentation skills nor did they deteriorate. Mahdi (2022) and Ahmad et al (2022) asserted that learners would have improved their presentation skills with the help of tools which could assist learners to boost their level of confidence and motivation leading to the improvement of their competency to do better presentations in the future. Chris (2016) found that learners were able to improve their self-confidence when they do more oral presentation practices within a non-threatening environment.…”
Section: L3: Generally I Can See Some Improvements In Terms Of the Co...mentioning
confidence: 99%
“…However, L4 could see some changes in certain groups of learners and she also shared how other learners did not improve their presentation skills nor did they deteriorate. Mahdi (2022) and Ahmad et al (2022) asserted that learners would have improved their presentation skills with the help of tools which could assist learners to boost their level of confidence and motivation leading to the improvement of their competency to do better presentations in the future. Chris (2016) found that learners were able to improve their self-confidence when they do more oral presentation practices within a non-threatening environment.…”
Section: L3: Generally I Can See Some Improvements In Terms Of the Co...mentioning
confidence: 99%